2003
DOI: 10.1159/000072139
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Phenotype in Allergic Asthma and Atopic Dermatitis

Abstract: Background: T cells are key regulators of immunologic disease parameters. However, their contribution to the process of tissue remodeling is ill defined. In the present study, we investigated gene expression of allergy-characteristic, IL-4-rich T cell cDNAs to monitor expression of genes that might participate in the pathogenesis of allergic diseases. Methods: cDNAs of freshly isolated and restimulated CD4+ T cells from patients with allergic asthma (AA) or atopic dermatitis (AD) and healthy subjects were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
2
28
0
1
Order By: Relevance
“…Identification of novel Th2-associated clusters in HDM-stimulated PBMC. PBMC from 20 atopics and 20 nonatopics were cultured in the presence or absence of HDM for the indicated time points (12,24, or 48 h). Total RNA was extracted and pooled into six separate groups: AT1 (pool of 5 atopics), AT2 (pool of 5 atopics), AT3 (pool of 10 atopics), NA1 (pool of 5 nonatopics), NA2 (pool of 5 nonatopics), NA3 (pool of 10 nonatopics).…”
Section: Study Design and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of novel Th2-associated clusters in HDM-stimulated PBMC. PBMC from 20 atopics and 20 nonatopics were cultured in the presence or absence of HDM for the indicated time points (12,24, or 48 h). Total RNA was extracted and pooled into six separate groups: AT1 (pool of 5 atopics), AT2 (pool of 5 atopics), AT3 (pool of 10 atopics), NA1 (pool of 5 nonatopics), NA2 (pool of 5 nonatopics), NA3 (pool of 10 nonatopics).…”
Section: Study Design and Statistical Analysesmentioning
confidence: 99%
“…Collectively, these studies indicate that individual immune responses typically involve up-regulation of multiple hundreds of genes (7)(8)(9). This technology has also been applied in the allergy field to study Th2 responses and related signaling pathways in freshly isolated T cells (10), polyclonally stimulated T cells (11,12), allergen-specific T cell clones and lines (13,14), polarized Th1/Th2 cell lines (15)(16)(17)(18)(19)(20), and in animal models (21). A consistent finding in the studies was the substantial number of differentially expressed genes identified, however, the lack of consistency in the gene lists reported by each study is striking.…”
mentioning
confidence: 99%
“…Wohlfahrt and colleagues (18), in another study of peripheral CD4 ϩ lymphocytes, comparing subjects with asthma with normal control subjects using cDNA microarray techniques, also found up-regulation of TGF-␤1 and other members of the TGF-␤ family. Furthermore, they found evidence for up-regulation of several other gene families in asthma, including those for chemokines, chemokine receptors, fibroblast growth factors, and matrix metalloproteinases and their inhibitors.…”
Section: Peripheral Blood Lymphocytesmentioning
confidence: 93%
“…15S-HETE may be involved in airway remodeling (16), whereas lipoxins are increasingly appreciated for their antiinflammatory properties (17). Likewise, detection of CX3CR1 is a novel finding, but was found previously to be elevated in peripheral CD4 ϩ lymphocytes of subjects with asthma compared with normal control subjects (18). Genes included in the serine proteinase inhibitor (serpin) family of protease inhibitors, such as cathepsin C and cathepsin G, were also identified as differentially regulated in subjects with asthma compared with control subjects, and their potential role in asthma has been supported by other expression profiling studies (19,20).…”
Section: Bronchial Biopsymentioning
confidence: 98%
“…For this technique, RNA from diseasespecific tissue is required. Previous studies have shown that peripheral blood mononuclear cells (PBMCs) reflect diseasespecific changes in an organ, and can be used as a model for the characterisation and monitoring of asthma using microarrays [18][19][20]. Unstimulated PBMCs most closely resembles the in vivo activation state of these cells [21].…”
mentioning
confidence: 99%